THE EFFECT OF LANGUAGE GAMES WITH AUDIO VISUAL AIDS ON STUDENTS’ SPEAKING COMPETENCE AT FOURTH GRADERS OF TUNAS DAUD ELEMENTARY SCHOOL - Susnawati, Kadek; A.A.I.N., Marhaeni (LPPM Undiksha, 2020)
This study aimed to determine the effect of language games with audio visual aids on students' speaking competence at fourth grade students of Tunas Daud elementary school and to describe the implementation of language games with audio visual aids on students? speaking competence. The design used in this research was a mixed method design. It was explanatory design since this research was started with quantitative design (experimental design with post test only control design) followed by qualitative design. The samples were 62 students; 31 students of the experimental group and 31 students of the control group of fourth grade Tunas Daud elementary students. The data were collected by using speaking competence test and analyzed by IBM SPSS 22 with independent t-test. The data were also collected through an observation sheet for observing the implementation of the language games with audio visual aids. The results showed there was a significant effect of the language games with audio visual aids on students' speaking competence in which the mean score of the students who were taught by using language games with audio visual aids is better than the students who were taught without language games with audio visual aids. For the implementation of the language games with audio visual aids, it can be seen that the implementation of the language games with audio visual aids were done in a very good way. The games was suitable for the students since it could give good impacts for the students. The students are active and confident to speak.